Tomato microbiome under long‐term organic and conventional farming. Issue 3 (19th August 2022) - Zhang, Zeyu; Xiao, Yang Sean; Zhan, Yabin; Zhang, Zengqiang; Liu, Youzhou; Wei, Yuquan; Xu, Ting; Li, Ji
Abstract : The compartment niche is the main reason behind the shifts in endophytic bacterial communities. Long‐term organic greenhouse exerted limited influence on the variations of endophytic bacterial communities. Organic greenhouse and root had more complex co‐occurrence networks than conventional greenhouse and stem, respectively. Cultivable method results found that Protecbacteria, Bacteriodes, and Actinobacteria are the dominant phyla in the endophytes.